"La Migra" in the Classroom: Transfronterizx Students Exploring Mobility in Transnational Higher Education on the US-Mexico Border. Issue 5 (3rd September 2018) - Convertino, Christina
Abstract : Based on an ethnographic study of a pre-engineering freshman course at a large university on the US-Mexico border, I explore how 4 Latinx undergraduate students, 2 of whom crossed the border on a daily basis to pursue higher education (HE), built a Lego robot that they named La Migra (a colloquial term for US Border Patrol). In particular, I demonstrate that the students drew from local authorized border crossing activities to design the robot to accelerate cross border mobility. In using the new mobilities paradigm (Sheller & Urry, 2006 ; Urry, 2007 ) and borderwork (Rumford, 2008 ), I also show that the design of the La Migra robot, rather than a public good, was actually symbolic of the uneven distribution of mobility. In total, findings contribute a particularistic account of the understudied significance of physical border crossing to mobility in the context of transnational HE.